Business purpose in tax relations: regulatory and applied scientific analysis - Pilipenko, Aleksandr A. (Journal of the Belarusian State University. Law, 2019)
The theoretical and practical questions of a business purpose in tax relations are investigated. Based on the analysis, the author’s definition of a business purpose was developed, the need to work out criteria for distinguishing between legitimate and unlawful tax optimization was postulated, and proposals and directions for improving national legislation were determined.
Keywords: business purpose; tax savings; profits; legal qualifications; tax base; tax base adjustment